The mechanisms of movement preparation: a precuing study - Bock, Otmar; Eversheim, Udo (Behavioural brain research, 2000)
It is well known that precues about the possible locations of upcoming targets reduce the manual reaction time. The present study investigates at which stage of the sensorimotor system such precues act. Several light dots were displayed as a precue; one of them became the target, and subjects had to produce a manual response to the target as fast as possible. Exp. A varied independently the number of precues and the area of space they occupy; we found that the reaction time of pointing movements depended on spatial extent, but not on the number of choices. The outcome was similar in Exp. B, where subjects produced stereotyped ‘tapping’ movements irrespective of target position. Taken together, both findings support the view that precues act mainly at a stage concerned with the internal representation of space, rather than with response selection or movement preparation. The effects of precues were preserved when subjects fixated throughout the precuing period (Exp. C), but not when precue and target positions were uncorrelated (Exp. D). These findings do not support the alternative interpretations, that precues act by guiding the eyes into the vicinity of targets, or by elevating the subjects’ arousal level.